Effect of ion assistance on silicon nitride films deposited by reactive magnetron sputtering. (April 2023) - You, Daoming; Liu, Weihua; Jiang, Yu; Cao, Yingchun; Guo, Wentao; Tan, Manqing
Abstract: Silicon nitride films were deposited by reactive magnetron sputtering, during which ion assistance was introduced. The results showed that the optical properties and composition were significantly affected by ion assistance. The refractive index was decreased from 2.87 to 2.17, and the extinction coefficient was decreased from 0.1535 to 0.0031 (@492 nm). The nitrogen-to-silicon ratio was increased from 0.612 to 0.955 by ion assistance, shifting from silicon-rich to near-stoichiometric. Not only that, the ion-assisted film featured lower roughness and less impurity. As the ion source power increased, the Raman peaks of silicon and silicon oxide decreased as well. In this work, ion assistance exhibits a considerable effect on silicon nitride films, which has potential applications in the processing of silicon nitride films and other semiconductor thin films. Highlights: Ion-assisted reactive magnetron sputtering was introduced into silicon nitride film. The ratio of nitrogen to silicon increased from 0.612 to 0.955 with ion assistance. Refractive indies of films reduced from 2.87 to 2.17 at 492 nm with ion assistance. Roughness and impurities in silicon nitride films reduced with ion assistance. No significant flaws were introduced in films with ion assistance.